Research Work on Network Intrusion Detection Using Artificial Immune System (International Journal of Engineering and Computer Science, 2014)
An artificial immune system (AIS) is a computer software system that mimics some parts of the behavior of the human immune system to protect computer networks from viruses and similar cyber attacks. Artificial immune system is a computer software system that mimics some parts of the behavior of the human immune system to protect computer networks from viruses and similar cyber attacks. The essential idea is that the human immune system, which is a complex system consisting of lymphocytes. This work provides AIS based intelligence to provide security measures in intrusion detection system.